History of Anestesiology ad Resuscitation in Cienfuegos - Omar Rojas Santana; Evangelina Davila Cabo de Villa; Rosa Mirta Molina Lois; Indira Rojas Molina (Medisur)
As of the introduction of anesthesia on the Island, on March 11, 1847 there was a progressive advance in the development of surgery. In Cienfuegos it would be a milestone when the surgeon Alfredo Méndez introduced it between 1901 and 1902; and its use has increased at present. The main actions that have been developed by the Anesthesiology and Resuscitation specialty in the general hospitals in Cienfuegos were described. The book of the Clinical Anesthesiology, in its first and second editions, was revised. Interviews were conducted with protagonists who were part of the development of the specialty in Cienfuegos. The main facts that were developing the specialty of Anesthesiology and Resuscitation in the province were found since the beginning of the 20th century with the application of chloroform and ether by Alfredo Méndez surgeon and how it continues its development with doctors dedicated to anesthesia in the beginning of the second half of the 1950s; the development in the Civil Hospital and private clinics, until the triumph of the Revolution and until nowadays in the XXI century. Anesthesia in Cienfuegos was introduced at the beginning of the 20th century, having a constant task in the development of this discipline, as well as the integration of the specialty to the Anesthesiology Resuscitation and Pain Cuban Society, being its provincial group and chapter.